Impact of platinum-based and non-platinum chemotherapy on quality of life in non-small cell lung cancer: A narrative review - Yuditha Astarina, Davinda; Rahmawati, Fita; Murti Andayani, Tri (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2026)
Chemotherapy remains one of the main therapeutic options for patients with advanced non-small cell lung cancer (NSCLC), a disease that continues to contribute significantly to global cancer-related mortality. The selection of platinum-based or non-platinum chemotherapy regimens has important clinical implications, as these approaches differ not only in antitumor efficacy but also in their impact on patients’ health-related quality of life (HRQoL). This narrative review aimed to synthesize recent evidence regarding the effects of platinum-based and non-platinum chemotherapy on HRQoL among patients with NSCLC. Relevant studies published between 2020 and 2025 were identified through systematic searches of major scientific databases, including PubMed, Scopus, and Web of Science. The findings were narratively synthesized across commonly reported HRQoL domains using validated assessment instruments, such as the Functional Assessment of Cancer Therapy–Lung (FACT-L), the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) and Lung Cancer Module (QLQ-LC13), as well as the EQ-5D-5L. Overall, platinum-based chemotherapy was associated with better disease control but also with greater toxicity-related deterioration in physical and emotional functioning. In contrast, non-platinum regimens demonstrated improved tolerability and more stable HRQoL outcomes. These differences have important implications for shared clinical decision-making, particularly in patients with advanced disease for whom symptom relief and quality of life often represent primary treatment goals. This review highlights the need to integrate HRQoL considerations alongside clinical efficacy when individualizing chemotherapy strategies for patients with advanced NSCLC.